Performance of block Markov superposition transmission over non-Gaussian impulsive channels - Xiao MA; Meiying JI; Shengxiao CHEN (Tongxin xuebao)
Block Markov superposition transmission scheme was used over channels with symmetric alpha-stable (SαS) impulsive noise.Based on the equivalent genie-aided system,the lower bound of the block Markov superposition transmission system was analyzed.Numerical simulations over non-Gaussian impulsive channels with different characteristic exponents show that,in the low bit-error rate region,performance of the block Markov superposition transmission system matches well with the lower bound.Block Markov superposition transmission scheme performs well (with 0.85 dB away from Shannon limits at the BER of 10-5) over non-Gaussian impulsive channels.